2009
DOI: 10.1021/jp9017986
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Dependent Cage Dynamics of Small Nonpolar Radicals: Lessons from the Photodissociation and Geminate Recombination of Alkylcobalamins

Abstract: Time-resolved transient absorption spectroscopy was used to investigate the primary geminate recombination and cage escape of alkyl radicals in solution over a temperature range from 0 to 80 degrees C. Radical pairs were produced by photoexcitation of methyl, ethyl, propyl, hexylnitrile, and adenosylcobalamin in water, ethylene glycol, mixtures of water and ethylene glycol, and sucrose solutions. In contrast to previous studies of cage escape and geminate recombination, these experiments demonstrate that cage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 76 publications
4
59
1
Order By: Relevance
“…Caged radical pairs are produced by photodissociation from their parent molecule in a cage. Accounting for the differences between pDTO and the alkyl radicals, the values of τ RE measured in this work are several times smaller than the values of the cage escape time obtained in ref (46). In the same way, we assume that the re-encounters and rotation of pDTO very likely occur in molecular cages made of a dynamic network of tetrahedrally coordinated water molecules.…”
Section: Discussioncontrasting
confidence: 75%
“…Caged radical pairs are produced by photodissociation from their parent molecule in a cage. Accounting for the differences between pDTO and the alkyl radicals, the values of τ RE measured in this work are several times smaller than the values of the cage escape time obtained in ref (46). In the same way, we assume that the re-encounters and rotation of pDTO very likely occur in molecular cages made of a dynamic network of tetrahedrally coordinated water molecules.…”
Section: Discussioncontrasting
confidence: 75%
“…A compelling example is the homolytic cleavage of carbon-cobalt bond in 5′-deoxyadenosylcobalamin (coenzyme B 12 ) to form cobalt(II)-cobalamin and an adenosyl radical, which is important for the biological functions of coenzyme B 12 -dependent mutase enzymes. Time-resolved spectroscopic studies showed that the initial radical pair formed after Co–C bond homolysis in adenosylcobalamin undergoes in-cage radical recombination and cage escape both at approximately 10 9  s −1 , clearly indicating a competition between the two processes [124126]. …”
Section: The Intermediacy Of Substrate Radicals During C–h Activationmentioning
confidence: 99%
“…Ultrafast broadband transient absorption spectroscopy has been used to study the photochemistry and photophysics of naturally occurring and synthetically prepared cobalamin compounds [9,[15][16][17][18][19][20][21][22][23][24][25][26][27]. Alkylcobalamins are photolabile.…”
Section: Introductionmentioning
confidence: 99%
“…Alkylcobalamins are photolabile. For most alkylcobalamins that have been studied to date, the primary photolysis quantum yield is on the order of unity [15,21,22,24]. The quantum yield for long-lived radicals is determined by competition between diffusive separation of the radical pair and geminate recombination [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation